(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
This article presents scientific research on the effect of nitrogen fertilizer rates on the stem height of rice. The experiments were conducted under the conditions of the Khorezm region, providing data on the impact of fertilization norms on plant height in the soil and climate conditions. The findings revealed that plant growth depends on nitrogen nutrition, the amount of oxygen on the soil surface, air temperature, water temperature, and soil thickness. In production conditions, excessive use of nitrogen increases the tendency of plants to lodge. The best results were obtained when nitrogen fertilizers were applied at a rate of 150 kg of pure nitrogen per hectare under optimal conditions